A new method for the automatic identification of the dimensional features of vertebrae. Issue 1 (August 2015) - Di Angelo, L.; Di Stefano, P.
Highlights This paper proposes a new approach to determine the measure of human vertebrae. Typical approaches perform measurements with lack of repeatability and reproducibility. The proposed method is based on morphological features recognition from 3D high point density model of the vertebrae. The paper proposes unambiguous rules to identify geometric references and the associated dimensions. Compared to typical approaches, the proposed method proved to be more repeatable and reproducible.